Integrated feed forward system for chemical mechanical polishing oxide removal process automation to improve productivity - Ramlan, Samad (2022)
Chemical Mechanical Planarization (CMP) is one of the main processes in semiconductor wafer fabrication. It is the only process that has contact physically with the wafer, where a pad is placed directly onto the wafer and polished in a circular motion at a particular speed to planarize the wafer surface. For a typical CMOS devices, the downstream process for CMP is the film depositions process and the upstream is the lithography process in which both requires high precision machine capabilities. The process is repeated 10 to 15 times with 300 to 1000 process steps of a wafers cycle dependings on the Integrated Circuit device complexities. Due to the acceptance process tolerance which is measured at a nanometer level and with very tight process controls, excessive polishing on the oxide layer cannot be reworked. Therefore, there is a need to control and monitor closely for each recipe used to process the wafer. Additionally, SilTerra wafer fabrication facility is loaded with more than 200 devices that require to process 5000 to 6000 wafers daily. These devices require variations of processing sequences as well as different settings to be manually conducted. Subsequently, these devices eventually contribute to longer setup times, and commonly lead to human mistakes and equipment interruption of up to about 3000 events a year. That could lead to the need for further inspections or corrections of more than 60,000 wafers. The CMP process for this study is on oxide process. In order to achieve the consistency of an ideal process scenario which is to polish at the appropriate targeted removal rate, an integrated feed forward system is proposed to collect, integrate the information and automate the decision making process. This system is proposed to bridge the gaps particularly for process qualifications and the targeting procedures. Failure Mode and Effect Analysis (FMEA) method is applied to breakdown the process of obtaining the data, computing the data to as the input to the required parameter and applying the parameter to polish the wafers. From FMEA, it is then translated to feed forward system to collect and to integrate between process qualification data on non-production wafer until to apply targeting procedures on production wafers. Supporting functions are developed based on the SECS/GEM equipment interface protocol by Semiconductor Equipment Materials International (SEMI). Based on the observations and data collected, it is found that the system is successful in reducing the cycle time for about 17% from an average of 6 hours to 5 hours as well as reducing the wafers scrap rate from an average of 17 wafers per year to zero scrapped.